Peningkatan Keterampilan Dalam Bermain Drama Menggunakan Teknik Oscar Brocket (Teknik Observasi Imajinasi dan Teknik Panggung) Pada Siswa Kelas XI 2 SMA Negeri 6 Palembang - Syafika, Salsabila; Lestari, Hikmah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to help students improve their drama playing skills using the Oscar Brocket technique in class XI-2 students at SMA Negeri 6 Palembang. This research is classroom action research (PTK). The research subjects were students in class XI-2 SMA Negeri 6 Palembang, totaling 30 students. This research consists of two cycles. Each cycle consists of four stages, namely planning, implementation or action, observation, and reflection. Data collection techniques used were questionnaires, interviews, observations and documentation of learning activities. Analysis was carried out using qualitative descriptive techniques supported by quantitative data. The validity of the data obtained through validity (process, results and democratic). The results of this research show that the Oscar Brocket technique can improve drama playing skills in class XI-2 students at SMA Negeri 6 Palembang. This is based on the results of student observations from pre-action and Cycle I with a calculated average value of 4.33 (43.30%) and cycle II of 6.76 (67.60%). Students' drama playing abilities from the beginning to the second cycle increased to reach a calculated average of 2.43 (24.30%). Apart from that, progress in the drama learning process is also visible. Before the steps were implemented, students seemed to lack confidence in expressing themselves, were less active, often joked with classmates, and were less confident in playing the characters they played, so their performances were less than optimal. However, after these steps were implemented, students began to show improvements in expression, were more active, the learning atmosphere became more conducive, and students no longer hesitated in acting out the roles they took, and were even able to improvise in the characters they played and understand how to place their bodies in action.